Uji Usability Website Akademik Universitas XYZ Menggunakan User Experience Questionnaire (UEQ) - Novylia Dwi Wulanndari; Anwar Sodik (Institut Teknologi Adhi Tama Surabaya, 2023)
XYZ University Academic Website is a platform used by XYZ University students to find information related to lectures and academic activities. However, for now, the XYZ University educational website still needs some improvement in terms of interface, information availability, and user experience that still need to be improved. A Usability Test is carried out to measure the User Experience of a digital product. Testing is done by distributing questionnaires to students, which is the stage before changes are made to the website and have results such as Attractiveness (1.05), Efficiency (1.00), Clarity (1.15), Accuracy (1.09), Stimulation ( 1.21) and Novelty (0.96). Then an approach was taken using the design thinking method, and the following results were obtained: Attractiveness (1.51), Efficiency (1.41), Clarity (1.63), Accuracy (1.32), Stimulation (1.44), and Novelty ( 1,23).